КІНЕТИЧНІ ЗАКОНОМІРНОСТІ ПРОЦЕСУ КОНВЕКТИВНОГО СУШІННЯ СНЕКІВ ІЗ НАСІННЯ ЛЬОНУ - Sniezhkin, Yu. F.; Husarova, O.V. (Institute of Engineering Thermophysics of NAS of Ukraine, 2023)
The main component of the studied snacks is flax, which is rich in Omega 3, polyunsaturated fatty acids, fiber and vitamins A, B, E. The product does not contain emulsifiers, baking powder. The natural composition of raw materials limits the parameters of dehydration, requires such conditions of the process, which will preserve the most valuable components of the material. Careful analysis of the process kinetics is required to substantiate the rational drying parameters. The purpose of the work is to study the kinetics of moisture exchange depending on the process parameters; thermal audit of the operating convective drying unit; identifying ways to reduce energy costs during dehydration of snacks. Research methods. The study of the kinetics of the snack drying process was performed on an experimental convective stand with a system of automatic recording and processing of information at a drying agent temperature of 75, 90 and 90...80 ºC, speed 1.5 and 2 m/s, moisture content 11 g/kg dry air. Results. The results of experimental studies have shown that the use of step-wise dehydration mode 90…80 °C compared to one-stage drying at 75 °C leads to a process acceleration of 15%, and in the 90 °C mode - by 26%. Reducing the duration of the process by increasing the speed of the drying agent from 1.5 to 2 m/s at a temperature of 90 oC is almost non-existent.The organoleptic characteristics of the experimentally obtained snacks did not differ from those produced industrially and met the standards. Conclusions. Summarizing the results of thermal engineering audit and analysis of drying conditions of dehydrated material, rational regime parameters of the process are determined, additional structural elements of the dryer are developed and installed. Due to the improvement of the design of the drying unit, a uniform distribution of the flow rate of the drying agent, its temperature and moisture content is achieved. Such measures made it possible to intensify dehydration, reduce the duration of the process and reduce electricity consumption by 15…26%.